2022
DOI: 10.1111/cga.12465
|View full text |Cite
|
Sign up to set email alerts
|

Androgen/Wnt/β‐catenin signal axis augments cell proliferation of the mouse erectile tissue, corpus cavernosum

Abstract: The murine penile erectile tissues including corpus cavernosum (CC) are composed of blood vessels, smooth muscle, and connective tissue, showing marked sexual differences. It has been known that the androgens are required for sexually dimorphic organogenesis. It is however unknown about the features of androgen signaling during mouse CC development. It is also unclear how androgen-driven downstream factors are involved such processes. In the current study, we analyzed the onset of sexually dimorphic CC formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Sexual dimorphism of the size of the ExG becomes significant after birth and is induced via the androgen-Wnt/β-catenin signaling pathway [2]. It has been reported that Dkk2, which encodes an extracellular antagonist of canonical Wnt/β-catenin signaling, is expressed dominantly in female CC compared with the male CC at E16.5, leading to sexually dimorphic activation of β-catenin signaling [2]. A previous paper suggests that endothelial β-catenin signaling is a promoting factor in angiogenesis [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphism of the size of the ExG becomes significant after birth and is induced via the androgen-Wnt/β-catenin signaling pathway [2]. It has been reported that Dkk2, which encodes an extracellular antagonist of canonical Wnt/β-catenin signaling, is expressed dominantly in female CC compared with the male CC at E16.5, leading to sexually dimorphic activation of β-catenin signaling [2]. A previous paper suggests that endothelial β-catenin signaling is a promoting factor in angiogenesis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although urethral tube formation has been well discussed, the development of the penile corpus cavernosum (hereafter referred to as the CC) is not understood. The CC is one of the major structures in ExG developing at the upper (dorsal) part of penis by androgen dependently [2]. It is known as the erectile tissue, which contains arterioles, sinusoidal spaces composed of endothelial cells, smooth muscle, and extracellular matrix (ECM) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regulation of Sox9 is also critical in early staged mesenchyme as well as late staged male type CC formation 76 . Previous studies suggested the androgenic CC formation with sinusoids occurs in pubertal period 76 . Altogether, investigation of Sox9 and Wnt signal should be further studied in both stages, that is, sex‐independent and ‐dependent CC formation and pathogenesis.…”
Section: Regulators For Ectopic Chondrogenesis and Aging; Sox9 And Gr...mentioning
confidence: 99%
“…76 Therefore, regulation of Sox9 is also critical in early staged mesenchyme as well as late staged male type CC formation. 76 Previous studies suggested the androgenic CC formation with sinusoids occurs in pubertal period. 76 Altogether, investigation of Sox9 and Wnt signal should be further studied in both stages, that is, sex-independent and -dependent CC formation and pathogenesis.…”
Section: Reg Ul Ator S For Ec Topi C Chondrog Ene S Is and Ag Ing; So...mentioning
confidence: 99%
See 1 more Smart Citation